Here's the question you clicked on:
bobobobobobobobjsdfad
–2(m – 30) = –6m
First, distribute the -2 over the (m-30)
First, you distribute the -2 over, resulting in" \[-2m + 60\] Next, isolate m by adding 2m to both sides, resulting in \[60 = -4m\] After this, divide by -4 on both sides and you should have your answer for m. Check your work by plugging in your answer for m into the original equation and seeing if it balances out.
-2(m-30)=-6m distribute da -2 -2m-30=-6m subtract da -2m -30=4m divide by 4 -7.5=m
|dw:1357681242170:dw|
|dw:1357681374766:dw|
First you distribute, then you solve it like any other equation.